Planning Commission Study of Irrigation Codes and Acts - Committee on Plan Projects Planning Commission (Committee on Plan Projects Planning Commission Government of India, 1965)
This interim report reviews the existing irrigation codes and acts across Indian states, highlighting wide variations in legislative frameworks and irrigation management practices. Through a comparative analysis of select states, the study identifies key deficiencies in water regulation, maintenance of field channels, drainage management, assessment of water rates, and mechanisms for dispute resolution. The report emphasizes the need for standardized and modernized irrigation legislation to promote efficient water use, enforce scientific agricultural practices, and reduce losses due to poor infrastructure. Its recommendations provide a policy-oriented foundation for reforming irrigation laws to enhance agricultural productivity, ensure equitable water distribution, and address India’s growing challenges of water scarcity and food security.
An Interim Report Containing Preliminary Thinking on Some Aspects of the Study
Committee on Plan Projects (Irrigation Team) New Delhi November 1966
Keywords: Irrigation Codes; Irrigation Acts; Water Regulation; Canal Management; Drainage Systems; Water Rates; Agricultural Productivity; Legislative Reforms; Dispute Resolution; Water Allocation; Irrigation Infrastructure; Food Security